The Effect of PhET Simulation-Assisted Project-Based Learning Model on Students' Creative Thinking Skills in Elasticity Materials - Aris Doyan; Dian Faisal Hadi; Jannatin ‘Ardhuha (Postgraduate, University of Mataram, 2023)
The problems in this study are related to project-based learning models, PhET simulations, and students' creative thinking skills in elasticity material. This research is experimental, with pretest and posttest control designs. The population in this study were all students of class XI IPA SMAN 1 Wanasaba East Lombok, while the sample was class XI IPA II as the experimental class and class IPA I as the control class; each class had 31 students, which was in accordance with the sampling technique used, namely purposive sampling. The experimental class uses a project-based learning model assisted by PhET simulations, while the control class uses a conventional learning model. The test instrument used is a description of four items on elasticity. The results of the pre-test data analysis of students' creative thinking skills in the experimental class and the control class were not much different. After being given the treatment, the average value of the post-test experimental class was 68.80, and the average value of the control class was 65.51. The results of the post-test t test showed a significance (2 tailed) smaller than 0.050, so it could be concluded that the PjBL model assisted by the PhET simulation had an effect on the creative thinking skills of students on elasticity material.